Criminalidad organizada transnacional: de la seguridad pública a la amenaza geopolítica - Lagos Flores, Roberto (2024)
This article posits the hypothesis that transnational organized crime has evolved from a domestic public issue into a regional geopolitical threat. Employing a research methodology based on the analysis of secondary scientific sources and case studies, it scrutinizes the dynamics of organized crime at a regional level over the past five years. The primary arguments demonstrate that strategically significant criminal organizations have blurred national borders, forged both legal and illegal public and private alliances, expanded their operations, and primarily challenged the sovereignty, authority, legitimacy, monopoly of force, and territorial control inherent to States, thereby redefining the political geography. In conclusion, the study underscores the imperative to comprehend the radical nature and expansion of this transborder threat, along with its interaction with the institutional weaknesses of certain countries. It emphasizes the urgent need to enhance state capacities to confront this challenge, suggesting that governmental inaction and permissiveness could exacerbate the continental security crisis.